Hacia la gestión de la información corporativa y el e-gobierno en las Administraciones locales de las Islas Baleares (1997-2006) - Muñoz Cañavate, Antonio (Revista General de Información y Documentación, 2007)
During the past few years Spain’s Public Administrations have been undergoing an accelerated process of adapting their entire system of management to a reality structured around the Information Society. The present work studies that process of adaptation in the context of the Public Administrations of the Balearic Islands, in particular, of the Local Administration. It consists of five parts. The first briefly describes the process of transformation of the relationships between citizens and their Public Administrations and the importance of information in that interaction, and also sets the framework for the article. The second, which introduces us into the reality of the Balearic Islands, makes a brief reference to the Foundation IBIT as a motor of on-line communication projects. The third describes the degree of adaptation of Balearic citizens to this new form of communication with their Public Administrations as reflected in the indicators published by the Balearic Observatory of the Information Society. The fourth, describes the evolution from 1997 until the present of the entirety of the Town Councils of the Balearic Islands in their adaptation to the Web as an instrument of corporate communication, and analyzes through a study conducted by the Balearic Autonomous Community the status of the content of those corporate web sites. The fifth concludes the study by presenting a series of conclusions concerning above all the convergence between the reality described by the indicators of the citizens’ Internet use, and the presence of the Town Councils on the Web and the content of their sites.